Male phenotypic diversity experienced during ontogeny mediates female mate choice in guppies. (18th January 2019) - Macario, Alessandro; Croft, Darren P; Darden, Safi K
Abstract: Early social experience can be important in shaping female mate choice. Previous work has shown that females adjust their decisions based on the distribution of male sexual trait values encountered during development. However, other phenotypic features could be important in the formation of mate preferences if, for example, they provide additional information about the males available. Here, we examined how the level of overall phenotypic variance (independent of trait values) experienced during ontogeny, mediated female choice in guppies, Poecilia reticulata . Developing females were reared with males either all different in coloration or all similar in coloration or with adult females representing high variance, low variance, and no experience of male variance, respectively. We found that females were more sexually responsive when reared with females only than in either of the male treatments. When reared with males, responsiveness was greater in the low-variance treatment compared with the high-variance treatment. Moreover, females had stronger sexual preferences after rearing in the high-variance condition compared with the low-variance condition. In turn, males switched mating tactics, increasing the rate of coerced copulation attempts when facing choosier females, possibly to balance the loss in mating opportunities. Taken together, these results demonstrate the adaptive plasticity of female mating decisions and the dynamic selection pressures they might impose on the evolution of male sexual traits, potentially contributing to the maintenance of the extreme polymorphism found in male color patterns. Abstract : The social environment experienced as juveniles shapes female mate choice in guppies. We showed that females were more sexually responsive once adults if reared with females only. Moreover, growing females exposed to males looking all different in coloration increased the strength of their preference for male colors compared with females reared with males all similar in coloration. In response to females being choosier, males switched mating tactics increasing forced copulation attempts.